Leptospira interrogans and Leptospira kirschneri are the dominant Leptospira species causing human leptospirosis in Central Malaysia - Philip, Noraini; Bahtiar Affendy, Norliza; Ramli, Siti Nur Alia; Muhamad Arif; Raja, Pappitha; Nagandran, Elanngovan; Renganathan, Pukunan; Mohd Taib, Niazlin; Masri, Siti Norbaya; Yuhana, Muhamad Yazli; Thian, Leslie Lung Than; Seganathirajah, Mithra; et al. (Public Library of Science, 2020)
Background: Leptospirosis, commonly known as rat-urine disease, is a global but endemic zoonotic disease in the tropics. Despite the historical report of leptospirosis in Malaysia, the information on human-infecting species is limited. Determining the circulating species is important to understand its epidemiology, thereby to strategize appropriate control measures through public health interventions, diagnostics, therapeutics and vaccine development. Methodology/Principle findings: We investigated the human-infecting Leptospira species in blood and serum samples collected from clinically suspected leptospirosis patients admitted to three tertiary care hospitals in Malaysia. From a total of 165 patients, 92 (56%) were confirmed cases of leptospirosis through Microscopic Agglutination Test (MAT) (n = 43; 47%), Polymerase Chain Reaction (PCR) (n = 63; 68%) or both MAT and PCR (n = 14; 15%). The infecting Leptospira spp., determined by partial 16S rDNA (rrs) gene sequencing revealed two pathogenic species namely Leptospira interrogans (n = 44, 70%) and Leptospira kirschneri (n = 17, 27%) and one intermediate species Leptospira wolffii (n = 2, 3%). Multilocus sequence typing (MLST) identified an isolate of L. interrogans as a novel sequence type (ST 265), suggesting that this human-infecting strain has a unique genetic profile different from similar species isolated from rodents so far. Conclusions/Significance: Leptospira interrogans and Leptospira kirschneri were identified as the dominant Leptospira species causing human leptospirosis in Central Malaysia. The existence of novel clinically important ST 265 (infecting human), that is different from rodent L. interrogans strains cautions reservoir(s) of these Leptospira lineages are yet to be identified.